1979
DOI: 10.1037/0003-066x.34.8.682
|View full text |Cite
|
Sign up to set email alerts
|

Sexual intimacy in psychology training: Results and implications of a national survey.

Abstract: In a nationwide survey of members of APA Division 29 (Psychotherapy), which had a 48% return rate (N = 481), 10% of the respondents reported sexual contact as students with their educators; 13% reported entering sexual relationships as educators with their students. However, only 2% believed that such relationships could be beneficial to trainees and educators. Gender differences were significant: 16.5% of the women, compared with 3% of the men, reported sexual contact as students; however, 19% of the men, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
190
7
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(220 citation statements)
references
References 12 publications
(10 reference statements)
22
190
7
1
Order By: Relevance
“…But, some types of multiple relationships in the academic setting may easily be seen as exploitative. Studies have found that between 10 and 15% of psychology faculty acknowledged sexually intimate relationships with at least one student (e.g., Pope, Levenson, & Schover, 1979;Tabachnick, Keith-Spiegel, & Pope, 1991). Yet, 71% of faculty acknowledge that engaging in these relationships is unquestionably unethical (Tabachnick et al, 1991).…”
Section: Boundaries and Multiple Relationships In The Academic Settingmentioning
confidence: 99%
“…But, some types of multiple relationships in the academic setting may easily be seen as exploitative. Studies have found that between 10 and 15% of psychology faculty acknowledged sexually intimate relationships with at least one student (e.g., Pope, Levenson, & Schover, 1979;Tabachnick, Keith-Spiegel, & Pope, 1991). Yet, 71% of faculty acknowledge that engaging in these relationships is unquestionably unethical (Tabachnick et al, 1991).…”
Section: Boundaries and Multiple Relationships In The Academic Settingmentioning
confidence: 99%
“…Neben dem männlichen Geschlecht werden in der Literatur eine Reihe weiterer Charakteristika grenzverletzender Therapeuten aufgeführt, die als Risikofaktoren für sexuell übergriffiges Ver− halten gegenüber PatientInnen gewertet werden: Die Therapeu− ten sind häufig angesehen [13,17] und berufserfahren [11,18] in eigener Praxis tätig [16,19,20], befinden sich in schwierigen Le− benssituationen [18,21,22], haben narzisstische Defizite [23±25], weisen Problematiken im Umgang mit Nähe und Dis− tanz auf [21,26] und / oder sind selbst Opfer früherer Traumati− sierungen [27,28]. Auf Grundlage der Befunde ihrer Betroffenen− befragung Mitte der 1990er Jahre unterscheiden Becker−Fischer und Fischer [10,29] [36].…”
Section: Risikofaktorenunclassified
“…A literature review using PsyLit and Medline found only one survey of clients, that conducted by the American Consumer Reports magazine (Seligman, 1995). There have been surveys of psychotherapists focusing on the match of modality and client (Gibson, 1975), the difficulties of ending therapy with borderline patients (Sansone, Fine, & Dennis, 1991), the outcome of sex therapy (Kilmann et al, 1986), the management of memories of child sexual abuse (Poole et al, 1995), the significance of suggestibility for recovery of such memories (Yapko, 1994), attitudes to treatment manuals (Addis & Krasnow, 2000), experiences of personal therapy (Williams, Coyle, & Lyons, 1999), sexual contact during psychotherapy training (Pope, Levenson, & Schover, 1979) and the frequency of attack by clients (Guy, Brown, & Poelstra, 1990).…”
Section: Introductionmentioning
confidence: 99%